Cerebrolysin enhances spinal cord conduction and reduces blood-spinal cord barrier breakdown, edema formation, immediate early gene expression and cord pathology after injury - Sahib S.; Sharma A.; Menon P.K.; Muresanu D.F.; Castellani R.J.; Nozari A.; Lafuente J.V.; Bryukhovetskiy I.; Tian Z.R.; Patnaik R.; Buzoianu A.D.; Wiklund L.; Sharma H.S. (My University, 2025)
Spinal cord evoked potentials (SCEP) are good indicators of spinal cord function in health and disease. Disturbances in SCEP amplitudes and latencies during spinal cord monitoring predict spinal cord pathology following trauma. Treatment with neuroprotective agents preserves SCEP and reduces cord pathology after injury. The possibility that cerebrolysin, a balanced composition of neurotrophic factors improves spinal cord conduction, attenuates blood-spinal cord barrier (BSCB) disruption, edema formation, and cord pathology was examined in spinal cord injury (SCI). SCEP is recorded from epidural space over rat spinal cord T9 and T12 segments after peripheral nerves stimulation. SCEP consists of a small positive peak (MPP), followed by a prominent negative peak (MNP) that is stable before SCI. A longitudinal incision (2 mm deep and 5 mm long) into the right dorsal horn (T10 and T11 segments) resulted in an immediate long-lasting depression of the rostral MNP with an increase in the latencies. Pretreatment with either cerebrolysin (CBL 5 mL/kg, i.v. 30 min before) alone or TiO2 nanowired delivery of cerebrolysin (NWCBL 2.5 mL/kg, i.v.) prevented the loss of MNP amplitude and even enhanced further from the pre-injury level after SCI without affecting latencies. At 5 h, SCI induced edema, BSCB breakdown, and cell injuries were significantly reduced by CBL and NWCBL pretreatment. Interestingly this effect on SCEP and cord pathology was still prominent when the NWCBL was delivered 2 min after SCI. Moreover, expressions of c-fos and c-jun genes that are prominent at 5 h in untreated SCI are also considerably reduced by CBL and NWCBL treatment. These results are the first to show that CBL and NWCBL enhanced SCEP activity and thwarted the development of cord pathology after SCI. Furthermore, NWCBL in low doses has superior neuroprotective effects on SCEP and cord pathology, not reported earlier. The functional significance and future clinical potential of CBL and NWCBL in SCI are discussed. © 2020 Elsevier B.V.